2021
DOI: 10.1002/jwmg.22103
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Effects of Black‐Tailed Prairie Dogs on Livestock Grazing Distribution and Mass Gain

Abstract: The conservation and management of black‐tailed prairie dogs (Cynomys ludovicianus) have been contentious issues in grasslands of central North America for much of the past century, primarily because of the perception that they compete with livestock for forage. Studies quantifying the magnitude of competition between prairie dogs and cattle are difficult to conduct because of the large spatial and long temporal scales needed to quantify how competition varies in response to interannual variation in precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…This results indicate that environmental variables play a stronger role than grazing and animal disturbances on vegetation in shortgrass-dominant grasslands and is in line with studies in similar ecosystems (Grinath et al, 2019;Jäschke et al, 2020;Török et al, 2018). Moreover, this strong environmental effect on vegetation is in line with a recent study from Augustine and Derner (2021), which suggested prairie dog disturbance did not impact cattle mass gain negatively due to the influence of topography, temporal and soil variability. It is also important to note that prairie dog disturbance had no effects on the CWM height and leaf area, traits that are usually associated with grazing pressure (Blumenthal et al, 2020;Díaz et al, 2006).…”
Section: Effects Of Prairie Dog Disturbance On Diversity and Cwm Meanssupporting
confidence: 91%
“…This results indicate that environmental variables play a stronger role than grazing and animal disturbances on vegetation in shortgrass-dominant grasslands and is in line with studies in similar ecosystems (Grinath et al, 2019;Jäschke et al, 2020;Török et al, 2018). Moreover, this strong environmental effect on vegetation is in line with a recent study from Augustine and Derner (2021), which suggested prairie dog disturbance did not impact cattle mass gain negatively due to the influence of topography, temporal and soil variability. It is also important to note that prairie dog disturbance had no effects on the CWM height and leaf area, traits that are usually associated with grazing pressure (Blumenthal et al, 2020;Díaz et al, 2006).…”
Section: Effects Of Prairie Dog Disturbance On Diversity and Cwm Meanssupporting
confidence: 91%
“…Ultimately, the model could be used to support strategic management planning that reduces the volatility of boom‐and‐bust cycles in BTPD. This may help maximize the benefits of this keystone species to associated wildlife communities and ecosystem functioning, while also minimizing costs to the ranching industry (Augustine & Derner, 2021; Crow et al, 2022; Sierra–Corona et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Extreme fluctuations in colony size and abundance negatively affect grassland ecosystems as plague‐driven crashes result in subsequent declines in species heavily reliant on BTPDs as prey, such as large predatory birds (Duchardt et al, 2022; Seery & Matiatos, 2000), or as creators of critical habitat through their herbivory and burrowing (Augustine & Skagen, 2014; Eads & Biggins, 2015). Conversely, colony expansion can conflict with livestock production as BTPDs compete with cattle for available forage (Augustine & Derner, 2021; Crow et al, 2022), particularly during drier periods (Connell et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although research supports the compatibility of managing rangelands for both livestock and biodiversity conservation (Augustine & Derner, 2021; Fuhlendorf et al, 2012; Riginos et al, 2012), the balance is delicate, and made increasingly complex on rangelands occupied by burrowing rodents such as prairie dogs ( Cynomys spp.). As with many burrowing mammals (Davidson et al, 2012), black‐tailed prairie dogs ( Cynomys ludovicianus ; from this point forward “prairie dog”) play an integral role as keystone species within the North American Great Plains.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their keystone role (Kotliar et al, 1999), prairie dogs are considered a nuisance or noxious species in some states in the USA because of their capacity to compete with livestock for forage, and they are lethally controlled throughout their range (Augustine & Derner, 2021; Derner et al, 2006; Miller et al, 2007; Wyoming Weed and Pest Council, 2019). Due to the combined effects of habitat loss and control efforts that began in the 19th century, prairie dogs currently occupy a small fraction of their historical range (Knowles et al, 2002; Luce, 2003).…”
Section: Introductionmentioning
confidence: 99%